2002
DOI: 10.1063/1.1495891
|View full text |Cite
|
Sign up to set email alerts
|

The addition of Sb as a surfactant to GaN growth by metal organic vapor phase epitaxy

Abstract: The role and effect of the isoelectronic center Sb on the structure and properties of GaN epilayers have been investigated. The gas phase Sb concentration was varied by changing the triethyl antimony/trimethyl gallium mole ratio over a wide range of concentrations while keeping other growth parameters constant. The Sb addition slightly improved the optical and structural properties of GaN epilayer at a low level of Sb incorporation, especially for the films grown under a high group V/III ratio conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 29 publications
(28 reference statements)
2
34
0
Order By: Relevance
“…Sb and Bi containing organometallics are already widely used in commercial and research reactors for doping (in group IV semiconductors) and alloying (in III/V semiconductors). The surfactant effects of Sb have been studied on GaInP [6][7][8][9][10][11][12], GaN [13][14][15], (GaIn)(NAsSb) [16], InGaAs [17], and GaAs [18,19]. Bi surfactant effects have been studied on GaInP [7,9], GaAs [19], InGaAs [20,17], InGaNAs [21], Si [22], and during the fabrication of InAs quantum dots [23].…”
Section: Introductionmentioning
confidence: 98%
“…Sb and Bi containing organometallics are already widely used in commercial and research reactors for doping (in group IV semiconductors) and alloying (in III/V semiconductors). The surfactant effects of Sb have been studied on GaInP [6][7][8][9][10][11][12], GaN [13][14][15], (GaIn)(NAsSb) [16], InGaAs [17], and GaAs [18,19]. Bi surfactant effects have been studied on GaInP [7,9], GaAs [19], InGaAs [20,17], InGaNAs [21], Si [22], and during the fabrication of InAs quantum dots [23].…”
Section: Introductionmentioning
confidence: 98%
“…Prior to that work, the maximum concentrations reported by gas-source MBE were x∼0.26% [14,15] at a growth temperature of 750°C and x∼1% [16] at 500°C, respectively. These results suggest that the solubility limit of As in GaN is a function of temperature [17]. Zhao, et al, [16], has suggested that As acts mainly as a surfactant for temperatures over 700 C and that the GaN surface morphology improved in the presence of As at these high temperatures.…”
Section: Introductionmentioning
confidence: 66%
“…Both Sb and As have been used as surfactants to stabilize the growth front during SiGe growth [19][20]. Zhang, et al, used Sb as a surfactant in MOVPE growth of GaN at temperatures of 1000-1100 C and found a slight improvement in the optical and structural properties, particularly for films grown under high V/III ratio conditions [17]. One expects the solid solubility of Sb in GaN to be low due to the large difference in covalent radii and electronegativity, even larger than those for As in GaN [21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that antimony works as a well-known surfactant in the epitaxial growth of various films, such as SiGe [23], GaNAs [24,25] and GaN [26], where it segregates to the growing surface and affects the surface properties, such as the surface energy, the reconstruction, and the surface kinetics. The fact that Sb segregation on the AlN surface was not observed in the case of PLD growth of AlN on Cu is explained, probably by the assumption that the AlN/Cu heterointerface provides more stable sites than the growing surface.…”
Section: Resultsmentioning
confidence: 99%